# Talk:Reverse Compose: Difference between revisions

Jump to navigation
Jump to search

(→g∘h⍨∘f⍨ is equivalent to f⍛g∘h: new section) |
No edit summary |
||

Line 1: | Line 1: | ||

== g∘h⍨∘f⍨ is equivalent to f⍛g∘h == | == g∘h⍨∘f⍨ is equivalent to f⍛g∘h == | ||

An alternative definition for [[before]] is mentioned in [[Function_composition]]: f⍨∘g⍨ | |||

Perhaps we should mention split-compose's alternative definitions in this article, like-wise. | |||

(Editorialized for clarity and addressed in [[split-compose]]). |

## Latest revision as of 12:33, 12 April 2022

## g∘h⍨∘f⍨ is equivalent to f⍛g∘h

An alternative definition for before is mentioned in Function_composition: f⍨∘g⍨

Perhaps we should mention split-compose's alternative definitions in this article, like-wise.

(Editorialized for clarity and addressed in split-compose).